2005
DOI: 10.1089/apc.2005.19.40
|View full text |Cite
|
Sign up to set email alerts
|

STD and HIV Counseling Practices of British Columbia Primary Care Physicians

Abstract: This study evaluated British Columbian primary care physicians' use of sexually transmitted disease (STD) and HIV counseling guidelines. The authors sought to assess barriers to integrated HIV and STD testing and counseling, with the objective of developing and revising practice guidelines to meet the needs of primary care physicians in diverse settings. The BC College of Physicians and Surgeons membership of general practice/family medicine practitioners was stratified by practitioner location; 1200 physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…On the one hand, practical tools, such as sufficient (financial) incentives and support, could be a possible motivation for more proactive testing practices, that is, of chlamydia tests as was shown in an intervention setting in England21 while productivity goals could discourage such practices 22. Increasing clinician experience with patients attending the GP for an STI-related consultation and use of standardised (online) protocol sheets may help improve the quality of care,23 24 as well as accessible and relevant continuing medical education 25. Raising awareness and increasing collaboration improved STI services in a US study 26.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, practical tools, such as sufficient (financial) incentives and support, could be a possible motivation for more proactive testing practices, that is, of chlamydia tests as was shown in an intervention setting in England21 while productivity goals could discourage such practices 22. Increasing clinician experience with patients attending the GP for an STI-related consultation and use of standardised (online) protocol sheets may help improve the quality of care,23 24 as well as accessible and relevant continuing medical education 25. Raising awareness and increasing collaboration improved STI services in a US study 26.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, several studies, including ours, have found that providers of health care and HIV testing services miss opportunities to provide services that might help MSM avoid infection. 31,[58][59][60][61][62][63] Of those who reported using a regular source of health care, depending on race/ethnicity, one third to one half of participants reported that no one at their source of care had ever discussed whether they should test for HIV. Of those who had tested HIV-negative in the past year, nearly half reported that they did not receive any counseling with their test, including half of those who subsequently acquired HIV and could have benefited from counseling.…”
Section: Discussionmentioning
confidence: 99%
“…65 Many professionals believed they were performing to a standard; however, such performance was not found on testing. 66 Health care professional/physician barriers Sixty-two studies identified professional characteristics or factors such as maturity of practice, 67-70 legal concerns, 71 boundaries, 72,73 or peer influence as barriers to implementation of guidelines and evidence.…”
Section: Limitations Of Barrier Studiesmentioning
confidence: 99%